GROWTH, PHENOLOGICAL, YIELD AND YIELD COMPONENTS EVALUATION OF SWEET ORANGE (Citrus sinensis L.) CULTIVARS IN RAYA AZEBO WOREDA OF SOUTHERN TIGRAY, ETHIOPIA - Wakuma Biratu; Haile Abebe; Mola Berhe; Kidane Tesfay; Haileslassie Gebremeskel; Mulashu Tuemay; Haregua Feleke; Jhon Hardy Purba (Universitas Tadulako, 2023)
Sweet orange (Citrus sinensis L.) is an important fruit produced and consumed worldwide and it’s an excellent source of vitamin C. However, citrus industry in Ethiopia is at an infant stage; which is particularly due to shortage of improved and adapted cultivars and their distribution. Considering these, six sweet orange cultivars were evaluated to select adapted, high yielding and quality cultivar/s. Different growth, phenological, yield and yield component data were collected and analyzed using SAS. Days to maturity was also highly significantly (p<0.01)) affected by cultivars in 2017 cropping year. Fruit weight without rind (flesh weight) and juice weight were highly significantly (p<0.05) affected by cultivars in 2018 harvesting year. Marketable yield, unmarketable yield, and total yield tree-1 were significantly affected by cultivars in both 2017 and 2018 harvesting year. O. Valencia is late matured cultivars which took 1622 days from planting to first harvest. While, P.W.N. is early matured cultivars with average number of days of 1104 from planting to first harvest. In 2017, Hamlin, gave the highest marketable fruit yield tree-1 (68.61 kg) and total yield tree-1 (68.94kg). Jaffa gave significantly the maximum marketable fruit yield tree-1 (197.24 kg) and total yield tree-1 (198.81 kg) in 2018 cropping year. In 2019 harvesting year, Hamlin gave the highest marketable (63.3 kg) and total (64.02 kg) fruit yield tree-1. In average Jaffa and Hamlin gave the maximum marketable fruit yield tree-1 from the three consecutive harvesting years with mean value of 95.38 kg and 72.24 kg respectively. So, in Raya Azebo, and other areas having similar agro-ecologies Jaffa and Hamlin cultivars are recommended. Further, studying the nutritional content and water requirements of these cultivars are suggested.